Knowledge and Behavior Relationships about Nutrition to Events Anemia in a Teenage Princess in Bulanjahe Village, District Barusjahe Karo Regency in 2019 - Hanry Anta Lesmana (Institute of Computer Science (IOCS), 2020)
Nutrition, also known as nutrition, is the study of food and its relationship to health. This study aims to determine the relationship between knowledge and behavior about nutrition on the incidence of anemia in adolescent girls. The independent variable is knowledge and behavior about nutrition and the dependent variable is the incidence of anemia in adolescent girls in Bulanjahe Village, Barusjahe District, Karo Regency in 2019. This type of research is a pre-experiment with the design of